(untitled) (Journal of Nepal Paediatric Society, 2014)
Introduction: Nutrition is of paramount importance for adequate growth and development of a child. Various routes of providing enteral nutrition to a paediatric patient are by nasogastric, nasojejeunal and gastrostomy which can be placed surgically or endoscopically. The objectives of this study were to review cases with percutaneous endoscopic gastrostomy (PEG) procedure and patient characteristics, indications, complications and outcome of PEG tube insertion in children at our center. Materials and Methods: This was a prospective study carried out in Sir Ganga Ram Hospital in New Delhi, India for a period of two years from August 2010 to August 2012. It included patients in whom PEG tube were placed during the study period and have had at least one year of post procedure follow up. Demograhic details, duration of procedure, complications, initial weight and height and then at 3 month, 6 months and 12 months of PEG tube placement were also recorded. Data between groups was compared using ANOVA and within groups across follow-ups was done using paired t-test. Results: Fourty six PEG insertions were performed during the study period, 26 twenty six conversions to BRT or Mickey button and ten PEG removals. The main indications for PEG insertion were Cerebral palsy with feeding difficulty (47.8 %). Erythema at the PEG insertion site was the most common complication (21%). There was significant improvement in the weight and height in all age group of patients at 3, 6 and 12 months post procedure with a p value <0.5. The average weight gain after 3, 6 and 12 months was 1.3 kg, 2.8 kg and 4.2 kg and the average height gain after 3, 6 and 12 months was 1.6 cm, 2.5 cm and 4.13 cm respectively. Conclusions: PEG is effective means for optimizing the nutritional goals of patients who are nutritionally debilitated with minimal complications. DOI: http://dx.doi.org/10.3126/jnps.v34i2.10960 J Nepal Paediatr Soc 2014;34(2):125-131